Thermal and flow characteristics of a channel formed by aligned round tube bank fins stamped with curve delta-winglet vortex generators. (1st December 2021) - Lin, Zhi-Min; Li, Sheng-Fan; Liu, Cai-Ping; Wang, Liang-Bi; Zhang, Yong-Heng
Highlights: A novel fin punched curve delta-winglet vortex generators (CDVGs) is reported. The influence of CDVGs' parameters on Nusselt number and friction factor is evaluated. CDVGs can lessen the size of the tube wake size and pressure drop, enhance heat transfer. CDVGs can increase the secondary flow strength then enhance heat transfer. The secondary flow strength is the main parameter to determine Nusselt number. Abstract: The primary purpose of present study is to reveal the roles played by CDVGs in vectoring the airflow and breeding longitudinal vortices for enhancing heat transfer. The thermal-hydraulic characteristics of a finned aligned round tube heat exchanger with stamped CDVGs were numerically studied by using the custom code with SIMPLE algorithm in a nonorthogonal curvilinear coordinate system. Four geometric parameters including vortex generator height, radial position, peripheral position and fin pitch, were programmed to ascertain parametric effects on fin side thermal performance, and the regression formulas of Nusselt number and resistance coefficient in the fin side passage with Reynolds numbers and four geometric parameters were secured. The findings suggest that the mean Nusselt number, resistance coefficient and secondary flow strength for the novel fin with CDVGs are all prevail over that in the reference plain fin under a certain Reynolds number. The body fitted CDVGs are ideally situated for finned round tube exchanger in aligned arrangement. The action of CDVGs can not only efficiently lessen the size of recirculation area behind tube but also produce strong longitudinal vortices, accordingly heighten evidently the fin side heat transfer ability in the recirculation zone. Using the studied optimum geometric parameters can make the thermal property factor up to 1.35 under the same pumping power constraint in comparison with the reference plain fin geometry when Reynolds number equals to 3000. This study can be a real application in compact heat exchanger with finned round tubes when heat transfer augmentation is under consideration.